National Wisdoms and the ASEAN Human Rights Legal Regime - Heribertus Jaka Triyana (Faculty of law Udayana University, 2017)
Recently, the discourse on the relation between local wisdom and human rights shows its relevance. This article describes and critically examines the human rights norms and procedures with regards to common local wisdoms to remedy and redress human rights problems in South East Asian countries. It takes an example of redressing problem in rights to development and also focuses on the application of the ASEAN agreement on Disaster Management Response to contextualize role and influence of local wisdoms to manage and to mitigate disaster response within the ASEAN human rights protection. This writing also highlights that human rights based approach is needed in the implementation of the ASEAN human rights norms and mechanisms in accordance to local wisdoms of respective countries where disaster occurs. Keywords: Wisdom, ASEAN, Human Rights.